High Mineralization Capacity of IDG-SW3 Cells in 3D Collagen Hydrogel for Bone Healing in Estrogen-Deficient Mice - Chen, Kaizhe; Zhou, Qi; Kang, Hui; Yan, Yufei; Qian, Niandong; Li, Changwei; Wang, Fei; Yang, Kai; Deng, Lianfu; Qi, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
Tissue engineering with 3D scaffold is a simple and effective method for bone healing after large-scale bone loss. So far, bone marrow-derived mesenchymal stem cells (BMSCs) are mostly used in the treatment of bone healing in animal models due to their self-renewal capability and osteogenic potential. Due to the mainly functional cells in promoting osteoid mineralization and bone remodeling were osteocytes. Thus, we chose an osteoblast-to-osteocyte transition cell line, IDG-SW3, which are not proliferative under physiological condition, and compared the healing capability of this cells to that of BMSCs in bone defect. In vitro, IDG-SW3 cells, revealed a stronger mineralization capacity when grown in 3D collagen gel, compared to that of BMSCs. Although both BMSC and IDG-SW3 can generate stable calcium-phosphate crystal similar to hydroxyapatite (HA), the content was much more enriched in IDG-SW3-mixed collagen gel. Moreover, the osteoclasts co-cultured with IDG-SW3-mixed collagen gel were easier to be activated, indicating that the IDG-SW3 grafting could promote the bone remodeling more efficiency in vivo. At last, in order to reduce the self-healing capability, we assessed the healing capability between the IDG-SW3 cells and BMSCs in osteoporotic mice. We found that the collagen hydrogel mixed with IDG-SW3 cells has a better healing pattern than what was seen in hydrogel mixed with BMSCs. Therefore, these results demonstrated that by promoting osteoblast-to-osteocyte transition, the therapeutic effect of BMSCs in bone defect repair could be improved.